2016
DOI: 10.1097/brs.0000000000001295
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Dynamic Stabilization With Direct Pars Repair via Wiltse Approach for the Treatment of Lumbar Spondylolysis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In order to avoid the drawbacks associated with fusion and rigid fixation, the Isobar TTL semi-rigid dynamic stabilization system is one of them. The Isobar TTL system was originally designed for fusion surgery to facilitate intervertebral fusion based on Wolff's law and provides spinal stabilization while preserving relatively constant mobility (± 2.25°) of the surgical segment, and the system is currently being used for single-segment non-fusion procedures with good clinical results [ 5 7 ]. However, there have been no reports of the Isobar TTL system being used in combine with posterolateral fusion for two-segment hybrid surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid the drawbacks associated with fusion and rigid fixation, the Isobar TTL semi-rigid dynamic stabilization system is one of them. The Isobar TTL system was originally designed for fusion surgery to facilitate intervertebral fusion based on Wolff's law and provides spinal stabilization while preserving relatively constant mobility (± 2.25°) of the surgical segment, and the system is currently being used for single-segment non-fusion procedures with good clinical results [ 5 7 ]. However, there have been no reports of the Isobar TTL system being used in combine with posterolateral fusion for two-segment hybrid surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Wolff’s law for fusion surgery, the original design concept of Isobar stabilization system is to promote interbody fusion [ 4 , 5 ]. And some clinicians have also successfully applied the Isobar dynamic stabilization system to non-fusion technology [ 6 – 8 ]. However, how much range of motion should be retained in dynamic stabilization, how to retain it, and which exercise method is more conducive to maintaining the physiological environment of the lumbar spine and slowing the degeneration of the adjacent vertebrae have always been problems that researchers from all over the world have been working to solve.…”
Section: Introductionmentioning
confidence: 99%
“…9,22,24 Many studies reported no complications at all associated with surgery. 30,35,36,42,44,53,58 The most commonly reported complications were wound site infection and extended postoperative pain, but even in these studies the incidence of complication represented the vast minority of patients. 22,26,29,37,45 The overall complication rate reported after fusion or other surgical repair includes very few cases of instrumentation failure, recurrent fracture, or pseudoarthrosis.…”
Section: Complication Ratementioning
confidence: 99%